Western North American Juniperus Communities A Dynamic Vegetation Type - van Auken, Oscar; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2008)
Juniperus woodlands and savannas in western North America are both extensive and dynamic, occupying approximately 55 million hectares. Various species of Juniperus have been increasing in density and are expanding into associated grasslands, reducing the size of the grasslands. The reason for the Juniperus expansion is highly debated, but seems to be related to high levels of herbivory, changing fire frequency and probably global change phenomena. Western North American Juniperus Communities addresses various aspects of the biology, ecology, and management of Juniperus woodlands and savannas, by synthesizing past, current, and proposed future research. The book includes information on community distribution, composition, and structure; the effects of alterations in ecosystem processes such as modifications in water budgets; and the impacts of humans, herbivory, and fire on the communities. The book will provide professionals with a solid background in Juniperus ecosystems, enabling them to better understand the communities and manage the communities for maximum sustained productivity and diversity. About the Editor: O. W. Van Auken is Professor in the Department of Biology at the University of Texas, San Antonio, Texas, USA.
Ecology -- Western North American Juniperus Communities: Patterns and Causes of Distribution and Abundance -- Structure and Composition of Juniperus Communities and Factors That Control Them -- Distribution of Juniperus Woodlands in Central Texas in Relation to General Abiotic Site Type -- Structure and Function of Woodland Mosaics: Consequences of Patch-Scale Heterogeneity and Connectivity Along the Grassland–Forest Continuum -- Comparison of the Understory Vegetation of Juniperus Woodlands -- The Potential Role of Mycorrhizae in the Growth and Establishment of Juniperus Seedlings -- Encroachment: Community Changes -- Ecological Impacts of Ashe Juniper on Subtropical Savanna Parklands and Woodlands -- Ecological Consequences of the Replacement of Native Grassland by Juniperus virginiana and Other Woody Plants -- Altered Ecosystem Processes as a Consequence of Juniperus virginiana L. Encroachment into North American Tallgrass Prairie -- Juniper Tree Impacts on Local Water Budgets -- Juniperus Woodlands and the Water Cycle on Karst Rangelands -- Management -- The Combined Influence of Grazing, Fire, and Herbaceous Productivity on Tree–Grass Interactions -- Ecological Consequences of Using Prescribed Fire and Herbivory to Manage Juniperus Encroachment -- From the Dust Bowl to the Green Glacier: Human Activity and Environmental Change in Great Plains Grasslands -- Reversing the Woodland Steady State: Vegetation Responses During Restoration of Juniperus-Dominated Grasslands with Chaining and Fire -- The Future -- Conclusions: Present Understanding and Future Research in Juniperus Communities.
Keywords: Ecology .; Environmental management; Plant ecology; Nature conservation; Forestry management; Landscape ecology; Ecology; Environmental Management; Plant Ecology; Nature Conservation; Forestry Management; Landscape Ecology